The Effect Of Time Management, Occupational Safety And Health (Osh) On Employee Work Productivity At Pt. Garuda Maintenance Facility Aero Asia Tbk - Fazira, Rabitha; Hasbi, Mochamad; Sugandha, Sugandha (Universitas Muhammadiyah Tangerang, 2025)
Productivity is an interdisciplinary approach to effectively determining goals. There is a low level of work productivity in the TRP production department at PT. GMF Aero Asia Tbk. Therefore, the objective of this study is to analyze the influence of time management, occupational health, and safety (OHS) on employee productivity.This research employs explanatory research method with a quantitative approach. The sample consists of TRP production department employees, using total sampling technique, with a known sample size of 82 individuals. Data analysis includes descriptive statistical analysis, instrument testing, regression analysis, and determination coefficient analysis. Data processing is aided by Microsoft Excel and SPSS software version 26.The research findings indicate that partially, time management variables have a positive and significant effect on work productivity, as evidenced by t-value 4.238 > t-table 1.990 and sig value 0.000 < 0.05. Occupational health and safety (OHS) variables do not have a positive and significant effect on work productivity, as evidenced by t-value 0.578 < t-table 1.990 and sig value 0.565 > 0.05. Simultaneously, time management variables, and occupational health and safety (OHS) have a positive and significant effect on work productivity, as evidenced by f-value 26.995 > f-table 3.11 and sig value 0.000 < 0.05. The R value is 0.637 indicating a